Ethnobotanical studies on plant resources of Mangowal, District Gujrat, Punjab, Pakistan - Muhammad Parvaiz (Mashhad University of Medical Sciences, 2014)
Abstract Objective: This study was conducted to collect indigenous traditional knowledge about the medicinal plants and their uses in Mangowal, District Gujrat, Punjab, Pakistan. Materials and Methods: The ethnomedicinal data were gathered through questionnaires and extensive personal dialogues with native individuals comprising 40 males and 20 females of diverse age groups between 50 to 80 years and also tabibs and hakims. Ethnobotanical investigations were directed from January 2013 to March 2013 under the acquiescence of university of Gujrat (UOG), Punjab, Pakistan. Results:  About 40 plant species belonging to 22 families were investigated which are utilized by native people to cure various disorders and ailments such as asthma, ulcer, gonorrhea, piles, stomach pain, and skin diseases. Medicinal plants comprises of combination of active compounds which are side effect neutralizing and synergistic. Herbal medicines were prepared from different part of plants. Mostly used plant parts were leaves, fruits, barks, roots, seeds, and sometimes whole plant. Conclusion: The results demonstrated that the area is rich in vegetation but remained botanically virgin and not explored extensively and intensively.